2005
DOI: 10.1177/10883576050200020401
|View full text |Cite
|
Sign up to set email alerts
|

Using Computer-Assisted Instruction and the Nonverbal Reading Approach to Teach Word Identification

Abstract: This study determined if the use of computer-assisted instruction Would be an effective method to promote Word identification using the Nonverbal Reading Approach (NRA). Three students With severe speech impairments and concomitant physical disabilities or autism Were provided decoding and Word identification instruction using the NRA across three conditions simulating the natural progression of classroom instruction from teacher-directed to computer-assisted instruction. The three conditions Were (a) teacher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
83
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 19 publications
6
83
0
Order By: Relevance
“…Specifically, seven of the studies targeted social behaviors (Bernard-Opitz et al 2001;Cheng and Ye 2010;Hetzroni and Tannous 2004;Murdock et al 2013;Sansosti and Powell-Smith 2008;Simpson et al 2004;Whalen et al 2006), nine studies targeted behavioral skills (Ayres et al 2009;Bereznak et al 2012;Cihak et al 2010;Flores et al 2012;Hagiwara and Smith-Myles 1999;Mancil et al 2009;Mechling et al 2006Mechling et al , 2009Soares et al 2009), and 12 studies targeted academic skills (Bosseler and Massaro 2003;Coleman-Martin et al 2005;Ganz et al 2014;Hetzroni and Shalem 2005;Pennington 2010;Schlosser and Blischak 2004;Simpson and Keen 2010;Smith 2013;Smith-Myles et al 2007;Soares et al 2009;Yaw et al 2011). The computer-assisted interventions implemented within the studies ranged in length from 3 to 30 sessions.…”
Section: Participant and Intervention Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, seven of the studies targeted social behaviors (Bernard-Opitz et al 2001;Cheng and Ye 2010;Hetzroni and Tannous 2004;Murdock et al 2013;Sansosti and Powell-Smith 2008;Simpson et al 2004;Whalen et al 2006), nine studies targeted behavioral skills (Ayres et al 2009;Bereznak et al 2012;Cihak et al 2010;Flores et al 2012;Hagiwara and Smith-Myles 1999;Mancil et al 2009;Mechling et al 2006Mechling et al , 2009Soares et al 2009), and 12 studies targeted academic skills (Bosseler and Massaro 2003;Coleman-Martin et al 2005;Ganz et al 2014;Hetzroni and Shalem 2005;Pennington 2010;Schlosser and Blischak 2004;Simpson and Keen 2010;Smith 2013;Smith-Myles et al 2007;Soares et al 2009;Yaw et al 2011). The computer-assisted interventions implemented within the studies ranged in length from 3 to 30 sessions.…”
Section: Participant and Intervention Characteristicsmentioning
confidence: 99%
“…For example, CAI for students with ASD have been demonstrated to increase: (a) object labeling and vocabulary acquisition (e.g., Coleman-Martin et al 2005;Massaro and Bosseler 2006), (b) correct letter sequences and spelling (e.g., Kinney et al 2003;Scholosser and Blischak 2004), (c) reading skills (e.g., Mechling et al 2007), (d) appropriate classroom behaviors (e.g., Mechling et al 2006;Whalen et al 2006), and (e) social skills (e.g., Simpson et al 2004;Sansosti and Powell-Smith 2008). From the information available, it appears that computers can be harnessed to support a wide variety of skills to children with ASD.…”
mentioning
confidence: 99%
“…The use of these systems has been shown to have positive effects on the acquisition of reading skills [5,6]; acquisition of vocabulary, language and listening skills [7]; on the treatment of dysgraphia [8]; and on learning mathematics [9][10][11]. Its effects have also been studied in cases involving ADHD.…”
Section: Learning Disabilities and Digital Toolsmentioning
confidence: 99%
“…The latest research has found that these tools can have positive effects on various aspects such as the acquisition of reading skills [5,6]; the development of vocabulary, language and listening skills [7]; treatment of dysgraphia [8]; mathematics learning [9][10][11]; and improvement in executive functioning in students with attention deficit hyperactivity disorder (ADHD) [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…There have been several studies investigating the use and efficacy of computer-based instruction (CBI) of reading skills to individuals with ASD [14][15][16][17][18][19][20].…”
mentioning
confidence: 99%